Factors that affect satisfaction towards e-learning among teachers - Cheok, Mei Lick; Wong, Su Luan; Mohd Ayub, Ahmad Fauzi; Mahmud, Rosnaini (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
In the new economic era, advancement of computer and networking technologies are fueling a transition in all educational institutions. Advances in e-learning technology and practice, are reshaping the way knowledge is constructed. In the Malaysian education scenario, e-learning is still at its infancy. Though only used currently as a compliment to the classroom teaching, there are a few issues and gaps that needed to be looked into. Lack of usage is the number one challenge which brings us to the issue of satisfaction. Many studies have shown satisfaction to influence continued usage of the e-learning system. This paper is a review of current studies, which focuses on factors that have been found to affect satisfaction.